Master course: educational pragmatism of higher educational establishments - Zagirniak , D. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
All universities in Ukraine have passed the licensing process, which allow them to train highly skilled professionals, including master's level. Then the accreditation procedure has passed, which confirmed the possibility of higher education to train masters. The vast majority of Ukrainian schools have passed both tests successfully. During two recent decades most educational establishments have increased the amount of licensed enrollment in the master course explaining it by a considerable demand. Somebody’s success inspired others to master new fields of knowledge. Increase of the amount of supply in particular specialties intensified the competition at this segment of the higher education services market. Each high school selects strategies and tactics, based on their own ability, on the one hand, and the market situation on the other. Conducted analysis of the capacity of Poltava region higher education institutions from the standpoint of individual and collective achievements allowed to find out how much pragmatism exeeds institutions’ ambition. The analysis revealed signs of pragmatism in the educational establishment activity concerning the master training, which demonstrates the level of realization of the establishment educational potential. It has been proved that “amount of licensed enrollment” index acquires a nominal character, so it is expedient to reduce its status from a normative to an approximate one. Educational establishments have in their nomenclature the commercially successful master training curricula that enable compensation for losses by other programs. The assessment of the absolute and relative pragmatism in the establishment activity concerning realization of master training programs proved that the number of competitors or their absence do not denote the ability of the establishments to realize their educational potential. It is not competition that determines the demand for the establishment educational pragmatism but the consumer’s behavior which is not always notable for pragmatism.